“The Hindu” and “Times of India” Representation of Aryan Khan Narcotic Drug Case from October 4th, 2021 to October 31st, 2021 - Betala, Sneha (Journal of Advanced Research in Journalism & Mass Communication, 2023)
How the general public views and responds to the use of illegal drugs is influenced by a wide range of factors. According to the agenda setting theory, a viewer is more likely to accept the media’s point of view as an accurate representation. As a result, news coverage, especially when it concerns the drug case involving a celebrity child of a superstar, greatly affects how people feel and act about using drugs, alcohol, and tobacco. Newspaper articles have the power to affect readers’ perceptions. The main objective of the research is to understand the representation and the frequency of certain words in the Aryan khan drug case. Comparative study was conducted and content analysis method was used to find out the tone of the newspapers. For the purpose of the study, two national newspaper The Hindu and Times of India were analyzed from October 3rd 2021 to October 31st 2021 that is from the time he was arrested till the time he was granted bail. How to cite this article: “The Hindu” and “Times of India” Representation of Aryan Khan Narcotic Drug Case from October 4th, 2021 to October 31st, 2021. J Adv Res Jrnl Mass Comm 2023; 10(2): 37-41. DOI: https://doi.org/10.24321/2395.3810.2023014